Procesamiento y presentación de datos de instrumentación de la presa del P.H. Pirrís - Granados-Alegría, Virginia (Instituto Tecnológico de Costa Rica, 2009)
The present work is based in the design and creation of a database in Microsoft Access, which will store the information from both types of instruments placed in the dam of PH Pirrís, as the data reported by each of them. This data, generated by the instruments, refer to the different behavior that shows the dam to the loading conditions to which it is subjected, in the construction process and service conditions. To achieve the design of the database was required to conduct a study on the types of instruments to be installed, as well as verify the exact location for each of them and their correct operation both before and after installation. After the design, creation an update of the database, a program in Microsoft Excel was developed, which allows displaying the information in a graphical form, so that designing engineers interpretation the dam behavior
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2009.
Keywords: Proceso; Construcción; Auscultación; Instrumentación; Concreto